Le Français sur Objectif(s) Universitaire(s) : un concept qui varie selon les contextes académiques - Gajewska, Elżbieta (Studia Romanica Posnaniensia, 2025)
The skills which determine the success of allophone students and which enable their integration into higher education are studied within the framework of specialized streams of language teaching for specific objectives, including Français sur Objectif Universitaire (FOU). So far, the only coherent and comprehensive description of this research stream comes from Mangiante and Parpette (2011). Their monograph devoted to FOU proposes methodological solutions and at the same time directs attention to certain key competences. Acquiring knowledge in a foreign language does not necessarily have to take place in the country of the target language. An example of studies conducted in a foreign language are philology studies at Polish universities: in English philology studies, this has been the case since the beginning of education. The article discusses the content of English for Academic Purposes presented to students during practical language learning classes, classes dedicated to the academic variety of English and diploma seminars. A similar study was conducted for FOU and the academic content proposed to students of Romance philology. The obtained results constitute an attempt to answer the question about the possibility of compiling a general set of content for FOU, and also contain proposals for Polish Romance philologies.